2017
DOI: 10.3389/fcimb.2017.00083
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Host Environment Alters Pseudomonas aeruginosa Susceptibility to Aminoglycoside Antibiotics

Abstract: During host infection, Pseudomonas aeruginosa coordinately regulates the expression of numerous genes to adapt to the host environment while counteracting host clearance mechanisms. As infected patients take antibiotics, the invading bacteria encounter antibiotics in the host milieu. P. aeruginosa is highly resistant to antibiotics due to multiple chromosomally encoded resistant determinants. And numerous in vitro studies have demonstrated the regulatory mechanisms of antibiotic resistance related genes in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Fourthly, oxidative stress induces efflux pump gene expression, promoting aminoglycoside tolerance [62]. Excessive ROS production has also been reported to lead to a reduced membrane potential and modification of LPS, which potentiates tobramycin activity [63].…”
Section: Mediators Of the Immune Responsementioning
confidence: 99%
“…Fourthly, oxidative stress induces efflux pump gene expression, promoting aminoglycoside tolerance [62]. Excessive ROS production has also been reported to lead to a reduced membrane potential and modification of LPS, which potentiates tobramycin activity [63].…”
Section: Mediators Of the Immune Responsementioning
confidence: 99%
“…Indeed, these studies denote that some antimicrobial agents are effective in vitro but not in vivo or vice versa. We and others previously demonstrated that lung epithelial cells modulate the activity of antibiotics in vitro [1519]. In particular, culturing biofilms of Pseudomonas aeruginosa on the surface of in vivo -like three-dimensional (3-D) lung epithelial cells enhanced the activity of aminoglycosides as compared to when these same biofilms were cultured on a plastic surface [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wu et al recently demonstrated that P . aeruginosa isolated directly from mouse lungs was more susceptible to aminoglycosides as compared to laboratory-grown cultures, suggesting that host factors influence antibiotic activity in vivo [15]. In the present study we aimed at elucidating (i) whether the host microenvironment influences aminoglycoside activity against bacterial pathogens, (ii) if host metabolites can potentiate aminoglycoside activity, and (iii) what the underlying mode of action is.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that V. parahaemolyticus uses similar mechanisms to establish colonization in the intestine of the host. Alternatively, the hostile environment in C. elegans may decrease the membrane potential of V. parahaemolyticus as observed in Pseudomonas aeruginosa 50 . If so, bacteria may upregulate the expression of genes involved in TCA cycle and ETC as a feedback to compensate the decrease in ATP production.…”
Section: Resultsmentioning
confidence: 99%